Cancer History and Systemic Anti-Cancer Therapy Independently Predict COVID-19 Mortality: A UK Tertiary Hospital Experience - Sng, Christopher C. T.; Wong, Yien Ning Sophia; Wu, Anjui; Ottaviani, Diego; Chopra, Neha; Galazi, Myria; Benafif, Sarah; Soosaipillai, Gehan; Roylance, Rebecca; Lee, Alvin J. X.; Shaw, Heather (Frontiers in Oncology, 2020)
Background: The COVID-19 pandemic remains a pressing concern to patients with cancer as countries ease social restrictions. It remains unclear whether cancer and its treatment contribute an independent risk for mortality in COVID-19. Methods: We included patients at a London tertiary hospital with laboratory confirmed SARS-CoV-2 infection. All patients with a history of solid cancer were included. Age- and sex-matched patients without cancer were randomly selected. Patients with haematological malignancies were excluded. Results: We identified 94 patients with cancer, matched to 226 patients without cancer. After adjusting for age, ethnicity and co-morbidities, patients with cancer had increased mortality following COVID-19 (HR 1.57, 95% CI:1.04-2.4, p = 0.03). Increasing age (HR 1.49 every 10 years, 95% CI:1.25-1.8, p <0.001), South Asian ethnicity (HR 2.92, 95% CI:1.73-4.9, p <0.001) and cerebrovascular disease (HR 1.93, 95% CI:1.18-3.2, p = 0.008) also predicted mortality. Within the cancer cohort, systemic anti-cancer therapy (SACT) within 60 days of COVID-19 diagnosis was an independent risk factor for mortality ( HR 2.30, 95% CI: 1.16 - 4.6, p = 0.02). Conclusions: Along with known risk factors, cancer and SACT confer an independent risk for mortality following COVID-19. Further studies are needed to understand the socio-economic influences and pathophysiology of these associations.